The Effect Of Service Quality On Customer Satisfaction Of Brilink Parmono Agents In Bangko Sempurna District , Rokan Hilir Regency - Thiara Amalia Fadly; M. Irwansyah Hasibuan (International Journal of Business and Quality Research, 2026)
This study aims to analyze the effect of service quality on customer satisfaction at BRILink Agent Parmono in Bangko Perfect District, Rokan Hilir Regency. The research method used is descriptive quantitative with a sample of 75 respondents selected through purposive sampling technique based on the Slovin formula. Data were collected through a closed questionnaire with a five-point Likert scale and analyzed using validity tests, reliability tests, simple linear regression analysis, hypothesis testing (t-test), and coefficient of determination (R²) with SPSS version 26. 0.05. The coefficient of determination (R²) of 0.897 indicates that service quality explains 89.7% of the variation in customer satisfaction, while the remaining 10.3% is influenced by other variables outside this study. The regression coefficient of 0.531 indicates that every one-unit increase in service quality will increase customer satisfaction by 0.531 units. These findings suggest that the better the service quality provided, the higher the customer satisfaction at BRILink Agent Parmono .